PERANAN HUKUM DESA ADAT BEGAWAN TERKAIT PENCEGAHAN ALIH FUNGSI LAHAN DI KAWASAN ALIRAN SUNGAI AYUNG - I Made Hendra Wijaya; IDA AYU AGUNG APSARI; Putu Gd. Bayu Suta Pratama; I WAYAN NADI SUMANTA; Kadek Krismayanti (Faculty of Law, Mahasaraswati University, Denpasar, 2020)
The importance of the existence of Begawan Adat Village located in Payangan Subdistrict of Bali Province in maintaining the Ayung River watershed which aims to prevent land conversion, so that the Ayung River Basin does not become damaged and disrupt the lives of the people and ecosystems in the area. In terms of protecting the Ayung watershed, the village of Adat Begawan needs customary law as an umbrella in legalizing the actions of the people of the Adat Begawan village in protecting the Ayung river basin. Customary law owned by the Begawan Adat village is in the form of Awig-awig, and Pararem, as well as some customs which are usually contained in the Dresta, where all the customary laws in the Begawan traditional village are based on the Tri Hita Karana concept in protecting the Ayung River Basin.